Evaluation of awareness level of indian graduate aspirants towards entrepreneurship and intrapreneurship concepts: A selective study - Srikanth, Akondi (Journal of Management and Science, 2013)
This paper seeks to know the awareness level of Indian graduate aspirants towards Entrepreneurship and Intrapreneurship concepts. Under descriptive research, survey method was conducted at a selective institution in Andhra pradesh. A sample of 129 out of 573 was drawn using proportionate stratified random sampling technique, out of which 113 had filled the forms and the leftover 16 were absent at the time of survey. The data was collected using schedule with 13 questions and the data analysis was done using descriptive statistics measure and percentages. From the analysis, it was found that about 53.98% of graduates heard about Entrepreneurship and only 18.58% heard about Intrapreneurship. Very few graduates have designated that certain most significant motives, characteristics and skills required for becoming successful Entrepreneurs or Intrapreneurs. It was also identified that only 23.89% and 7.9% of the total 113 graduate aspirants were willing to become Entrepreneurs and Intrapreneurs correspondingly. The major limitation of the study was that the survey meant for the chosen institution and had excluded the discussion of financial sources for Entrepreneurs or Intrapreneurs, left for further research. Lastly, it was concluded that the graduates were not clearly aware of the concepts, there arises a need to implant the concepts for their growth and our nation aswell.